Antioxidative peptides from food proteins : a review. - Sarmadi, Bahareh H. (Elsevier, 2010)
Bioactive peptides, as products of hydrolysis of diverse food proteins, are the focus of current research. They exert various biological roles, one of the most crucial of which is the antioxidant activity. Reverse relationship between antioxidant intake and diseases has been approved through plenty of studies. Antioxidant activity of bioactive peptides can be attributed to their radical scavenging, inhibition of lipid peroxidation and metal ion chelation properties of peptides. It also has been proposed that peptide structure and its amino acid sequence can affect its antioxidative properties. This paper reviews bioactive peptides from food sources concerning their antioxidant activities. Additionally, specific characteristics of antioxidative bioactive peptides, enzymatic production, methods to evaluate antioxidant capacity, bioavailability, and safety concerns of peptides are reviewed.